Change in extreme precipitation events: Exposure and vulnerability in the Poyang Lake Basin, China - Zhan, Mingjin; Wu, Qiong; Zhan, Longfei; Xin, Jiajie (Frontiers in Earth Science, 2023)
On the basis of daily observations data from 1984 to 2020, the spatiotemporal characteristics of extreme precipitation events in the Poyang Lake Basin (China) were analyzed using the intensity–area–duration method. With consideration of spatially distributed data on gross domestic product (GDP), population, and disaster losses related to historical extreme precipitation events, the exposure and vulnerability of the population and GDP of the study area to extreme precipitation events were systematically assessed. The results revealed the following. 1) The intensity and frequency of extreme precipitation, as well as the area affected, showed trends of increase, especially in the northeast of the basin. 2) Population exposure in the basin showed a trend of increase of 2.43 million/a. Change in population exposure was greatest in the most recent 10 years, with an average increase of 6.64 million/a. Change in extreme precipitation was the primary driver of the rapid increase in population exposure. 3) The average annual GDP exposure of the basin was ¥5.43 billion, and economic exposure has increased substantially at an average rate of ¥0.56 billion/a. Unlike population exposure, the increase in economic exposure was driven mainly by rapid economic growth. 4) By constructing vulnerability curves of economic losses in different decades, the trend of economic vulnerability was found to have clearly declined, i.e., economic vulnerability in 2010 was 13.3 (4.1) times lower than that in the 1990s (2000s). Effective disaster prevention and reduction measures should urgently be adopted in the study area to mitigate the effects of increase in extreme precipitation events.